2010
DOI: 10.1177/0363546509358319
|View full text |Cite
|
Sign up to set email alerts
|

The Distal Triceps Tendon Footprint and a Biomechanical Analysis of 3 Repair Techniques

Abstract: Anatomic repair better restores preinjury anatomy compared with other types of repairs and demonstrates less repair-site motion, which may play a role in early postoperative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 15 publications
5
113
0
Order By: Relevance
“…Because this study is an addition to the already published article by Yeh et al, 11 a simple paired Student t test was used to compare the 2 repair techniques regarding cyclic displacement, load at yield, peak yield, and stiffness.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because this study is an addition to the already published article by Yeh et al, 11 a simple paired Student t test was used to compare the 2 repair techniques regarding cyclic displacement, load at yield, peak yield, and stiffness.…”
Section: Methodsmentioning
confidence: 99%
“…After debridement of any grossly pathologic tendon tissue, one No. 2 highstrength nonabsorbable suture was used to suture the triceps tendon in locking Krakow fashion with 5 passes up and down starting and ending at the distal triceps tendon tip medially and laterally, as previously described by Yeh et al 11 The triceps footprint was identified, and crossed 2-mm tunnels were drilled from the proximal footprint to the dorsal ulnar surface, taking care to avoid entering the ulnohumeral joint. A suture passer was then used to pass the medial and lateral strands through the crossed tunnels.…”
Section: Surgical Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional fourth head of the triceps muscle has sporadically been reported arising from the posteromedial aspect of the proximal humerus [14,15]. The distal confluence of the muscular heads constitutes the distal tendon proper of the triceps brachii, which inserts 12 mm distal to the tip of the olecranon process of the ulna over an area of 466 mm 2 [16].…”
Section: Anatomy Reviewmentioning
confidence: 99%
“…Most recently, Yeh et al 12 compared the anatomic and biomechanical properties of the standard transosseous cruciate suture technique with both a single-row 2esuture anchor repair and their "anatomic" transosseous-equivalent repair method featuring 4 suture anchors in a double-row configuration. They showed better footprint coverage and decreased gap formation with their anatomic repair, as well as a trend toward increased load to yield that did not reach statistical significance.…”
mentioning
confidence: 99%